Large‐Area Low‐Cost Multiscale‐Hierarchical Metasurfaces for Multispectral Compatible Camouflage of Dual‐Band Lasers, Infrared and Microwave. (5th July 2022) - Feng, Xingdong; Pu, Mingbo; Zhang, Fei; Pan, Rui; Wang, Si; Gong, Jintao; Zhang, Renyan; Guo, Yinghui; Li, Xiong; Ma, Xiaoliang; Luo, Xiangang
Abstract: Multispectral complementary detection technologies have made single‐band camouflage materials ineffective, creating strong demand for multispectral compatible camouflage materials. Here, multiscale‐hierarchical metasurfaces (MHM) compatible with large‐area low‐cost fabrication are proposed for the first time to realize multispectral camouflage of dual‐band lasers, infrared and microwave. The MHM consists of an all‐metallic metasurface array (AMMA) and a microwave absorber. The AMMA hinders dual‐band lasers and thermal infrared detection, while the microwave absorber beneath the AMMA is applied as a defence against microwave detection. As a proof‐of‐concept, a MHM sample with an area of 30 × 30 cm 2 and a minimum linewidth of 1.8 µm is fabricated based on nanoimprint lithography. The excellent multispectral camouflage performance is verified in experiments, showing low reflectance (<0.2) in 0.9–1.2 µm and 9–12 µm, low infrared emissivity (<0.2), and high absorption efficiency of over 90% 2.7–26 GHz. Wide‐angle and polarization‐independent characteristics are also demonstrated. This work offers a promising opportunity for the engineering application of metasurfaces in the multispectral camouflage field. Moreover, this methodology can be easily extended to other electromagnetic spectrum, providing significant guidance for the design and fabrication of multispectral devices. Abstract : A novel strategy is proposed to realize multispectral compatible camouflage by using multiscale‐hierarchical metasurfaces. This is the first report on the use of metasurfaces to achieve laser‐infrared‐microwave compatible camouflage. The presented approach not only breaks through the limitation of conventional compatible camouflage materials in performance but also opens an exciting route to achieving large‐area low‐cost fabrication of multispectral camouflage materials.